A European study investigating patterns of transition from home care towards institutional dementia care: the protocol of a RightTimePlaceCare study - Verbeek Hilde; Meyer Gabriele; Leino-Kilpi Helena; Zabalegui Adelaida; Hallberg Ingalill; Saks Kai; Soto Maria; Challis David; Sauerland Dirk; Hamers Jan PH (BMC, 2012)
Abstract Background Health care policies in many countries aim to enable people with dementia to live in their own homes as long as possible. However, at some point during the disease the needs of a significant number of people with dementia cannot be appropriately met at home and institutional care is required. Evidence as to best practice strategies enabling people with dementia to live at home as long as possible and also identifying the right time to trigger admission to a long-term nursing care facility is therefore urgently required. The current paper presents the rationale and methods of a study generating primary data for best-practice development in the transition from home towards institutional nursing care for people with dementia and their informal caregivers. The study has two main objectives: 1) investigate country-specific factors influencing institutionalization and 2) investigate the circumstances of people with dementia and their informal caregivers in eight European countries. Additionally, data for economic evaluation purposes are being collected. Methods/design This paper describes a prospective study, conducted in eight European countries (Estonia, Finland, France, Germany, Netherlands, Sweden, Spain, United Kingdom). A baseline assessment and follow-up measurement after 3 months will be performed. Two groups of people with dementia and their informal caregivers will be included: 1) newly admitted to institutional long-term nursing care facilities; and 2) receiving professional long-term home care, and being at risk for institutionalization. Data will be collected on outcomes for people with dementia (e.g. quality of life, quality of care), informal caregivers (e.g. caregiver burden, quality of life) and costs (e.g. resource utilization). Statistical analyses consist of descriptive and multivariate regression techniques and cross-country comparisons. Discussion The current study, which is part of a large European project 'RightTimePlaceCare', generates primary data on outcomes and costs of long-term nursing care for people with dementia and their informal caregivers, specifically focusing on the transition from home towards institutional care. Together with data collected in three other work packages, knowledge gathered in this study will be used to inform and empower patients, professionals, policy and related decision makers to manage and improve health and social dementia care services.